Pengalaman Siswa-Siswi SMP Dharma Loka dalam Melakukan Meditasi: Pengabdian Masyarakat - Alberd Alberto Ardiansyah; Julia Surya (Institut Nalanda, 2024)
This study explores the benefits of meditation for student achievement, focusing on the application of three components of information processing theory: cognitive processes, information storage, and executive cognition. The subjects of the study were randomly selected students from SMP Dharma Loka Pekanbaru. The service involved four meditation training sessions, including guided meditation and walking meditation techniques. The results showed that meditation helped students reduce stress, improve focus, and calm their minds. Participants reported improvements in cognitive abilities and emotional control. Observations over the four sessions indicated positive developments in students' attitudes and behaviors. This study confirms that meditation can be an effective tool for enhancing academic performance and emotional well-being among students. Overall, meditation proved to be a beneficial practice in supporting mental health and spirituality among students